Exploring the Indigenous Fashion and Cultural Heritage of the Walak Tribe in Mamberamo Tengah, Papua Pegunungan - Napius Kogoya; Manase Halitopo; Piter Mabel (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study aims to examine the forms, meanings, and functions of the indigenous fashion of the Walak Tribe as part of cultural heritage in Mamberamo Tengah, Papua Pegunungan. This research employed a qualitative approach with an ethnographic design. Data were collected through direct observation, semi-structured interviews, and documentation involving 20 purposively selected informants, including traditional leaders, elders, craftsmen, community members, and youth. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing, supported by triangulation to ensure data validity. The findings show that Walak traditional fashion consists of various clothing items, ornaments, and accessories made from natural materials used in customary ceremonies and cultural activities. Each element of traditional attire carries symbolic meanings related to identity, social status, bravery, and the relationship between humans, nature, and ancestors. Furthermore, traditional fashion functions as a cultural identity marker and a means of intergenerational transmission of cultural values, despite challenges from modernization and social change.